Effect of Organizational Culture, Pay Satisfaction, Job Satisfaction on Nurse Intention to Leave at Private Hospital Type D in Bantul - Dimas Sigit Widodo; Nur Hidayah; Siti Dyah Handayani (Universitas Muhammadiyah Yogyakarta, 2021)
The study aims to identify the effect of organizational culture, pay satisfaction, job satisfaction on nurse intention to leave at Private Hospital Type D in Bantul. This study used a quantitative approach with a crossectional design. Collecting data using an instrument in the form of a questionnaire. This study uses SEM method analysis techniques using AMOS software. The results showed that there is a positive effect of organizational culture (c.r. 5,048, p 0,000) and nurse pay satisfaction (c.r. 3,713, p 0,000) on nurse job satisfaction. There is a negative effect of organizational culture (c.r. -3,123, p 0,002) and nurse pay satisfaction (c.r. -2,336, p 0,019) on the nurse intention to leave. There is no effect of nurse job satisfaction (c.r. -0,916, p 0,36) to nurse intention to leave.